Testing for independence of irrelevant alternatives some empirical results - Fry, T.R.L.; Harris, Mark (SAGE PUBLICATIONS INC, 1998)
In a recent article, Zhang and Hoffman discuss the use of discrete choice logit models in sociological research. In the present article, the authors estimate a multinomial logit model of U.K. Magistrates Courts sentencing using a data set collected by the National Association for the Care and Resettlement of Offenders (NACRO) and test the independence of irrelevant alternatives (IIA) property using six tests. Conducting the tests with the appropriate large sample critical values, the authors find that the acceptance or rejection of IIA depends both on which test and which variant of a given test is used. The authors then use simulation techniques to assess the size and power performance of the tests. The empirical example is revisited with the inferences performed using empirical critical values obtained by simulation, and the resultant inferences are compared. The results show that empirical workers should exercise caution when testing for IIA.